BIOSENSORY EXPERIENCES AND MEDIA MATERIALITY - Fotopoulou, Aristea; O’Riordan, Kate (AoIR Selected Papers of Internet Research, 2015)
Nearly 30 years since the publication of the ‘Cyborg Manifesto’ (Haraway, 1985), visions of cyborg lives continue to propel narratives of consumer electronics. Implants, wearables and networks of devices to augment the human sensorium have become mundane. This paper examines how the imaginary of networked everything, and fantasy of seamless interoperability is connected to a growing market of consumer electronics. These devices cover a spectrum from health to leisure, ranging from counting steps to measuring blood sugar. In an intensification of the social media paradigm they shift modes of participation from creating a profile and uploading information, to creating the conditions for automated and indefinite data generation. Such systems are not interoperable nor are they likely to become so but the promise of joined up health and consumer systems managed through new smart networks is seductive. As an area of innovation with direct market application these devices have already created new markets, which blur the distinctions between medical health and leisure and bring the promise of new biosensory experiences. This paper draws on a media analysis, together with an examination of the interface with a specific wearable sensor (Fitbit); and auto-ethnographic material. It draws these materials together with a synthesis of theoretical work on media materiality (Kember and Zylinska 2012), health (Lupton 2014), and imaginaries (Haran and McNeil, 2015 Jasanoff 2015,). The paper offers a way of thinking about different kinds of materiality and imaginary through these object and interface relations.